IMPROVING TEACHERS' ABILITY IN USING WHATSHAPP VOICE NOTE FACILITIES AS A MEDIA FOR DISTANCE LEARNING THROUGH INTEGRATED GUIDANCE ACTIVITIES AT SD BOROSUCI KAPANEWON KALIBAWANG KABUPATENKULON PROGO ACADEMIC YEAR 2020/2021 - Suprihatin Suprihatin (Universitas Islam Indonesia, 2021)
ABSTRACT: This study aims to determine and describe the teacher's ability to use the WhatsApp Voice Note application program in the distance learning process through integrated mentoring. The sample in this study was 9 teachers consisting of 6 classroom teachers and 3 subject teachers who were selected based on criteria using the WhatsApp Voice Note application program. This research was conducted in 2 cycles. Each cycle consists of 2 meetings and research procedures include; planning, implementation, observation and reflection. Meanwhile, to find out the teacher's activities at work, the researchers completed measuring instruments with observation instruments based on their ability to use the WhatsApp Voice Note application. The next aspect observed was the implementation of mentoring activities for researchers (principals). The results of the first cycle of research on the teacher's ability to use WhatsApp Voice Notes in Distance Learning obtained the lowest average score of the first cycle of 70.86%, the conversion value of 3, the